Light Emission From Hydrogenated and Unhydrogenated Si-Nanocrystal/Si Dioxide Composites Based on PECVD-Grown Si-Rich Si Oxide Films - Comedi, David; Zalloum, Othman H. Y.; Wojcik, Jacek; Mascher, Peter (IEEE JOURNAL OF SELECTED TOPICS IN QUANTUM ELECTRONICS, 2006)
Hydrogenated and unhydrogenated Si-nanocrystal/Si dioxide (Si-nc/SiO2) composites were obtained from SiyO1−y (y = 0.36, 0.42) thin films deposited by plasma-enhanced chem- ical vapor deposition. The unhydrogenated composites were fab- ricated by promoting the Si precipitation through the thermal an- nealing of the films in the flowing pure Ar at temperatures up to 1100 ◦C. The hydrogenated composites were obtained from identi- cal films by replacing the Ar with (Ar + 5% H2) in the annealing step. The photoluminescence (PL) of the composites was studied as a function of the annealing temperature (T ), annealing time, and pump laser power. The PL intensity increases with increasing annealing temperature and time; however, it increases faster and attains several hundreds percent larger values when the anneal- ing is performed under (Ar + 5% H2) as compared to the an- nealing under pure Ar. Fourier-transform infrared spectra show that H in these hydrogenated samples incorporates mainly as Si– H bonds. The dependence of the PL spectra on y, T , and laser power are consistent with the assumption that light emission in both the hydrogenated and unhydrogenated Si-nc/SiO2 compos- ites originates from the bandgap transitions involving the electron quantum confinement in the Si-ncs. The PL spectra from the hy- drogenated films are skewed to the red as compared to those from the unhydrogenated ones. The bulk of the data indicates that H passivates the nonradiative recombination centers, most probably Si dangling bonds in disordered Si-nc/SiO2 regions, thus increas- ing the number of Si-ncs that contribute to the PL and modifying the distribution of the emission wavelengths. Index Terms—Nanotechnology,photoluminescence (PL),plasma chemical–vapor deposition (CVD), semiconductor films, silicon.